Self-healing for the long haul: In situ automation delivers century-scale fracture recovery in structural composites - Jack S. Turicek; Zachary J. Phillips; Kalyana B. Nakshatrala; Jason F. Patrick (Proceedings of the National Academy of Sciences, 2026)
Nature’s structural composites, such as bone and wood, achieve mechanical performance through hierarchical multimaterial design. Though, their real vantage lies in the exceptional ability to repeatedly heal after damage. Synthetic fiber-reinforced polymer (FRP) composites also leverage material hierarchy via fibrous reinforcement encapsulated within a polymer matrix, maximizing stiffness and strength. However, the layered architecture of laminated FRP composites makes them vulnerable to interlaminar delamination—debonding of fibers from the matrix—which significantly compromises structural integrity. Recently, we introduced a self-healing strategy via in situ heating, where soft yet tough thermoplastic inclusions achieve interlaminar fracture recovery via polymer chain re-entanglement, i.e., thermal remending. Here, in our latest embodiment, by automating in situ thermo-mechanical experiments, we achieve an order-of-magnitude enhancement in self-healing repeatability—reaching an unprecedented 1,000 cycles. Healing begins at 175% and slowly declines to 60% of the mode-I fracture resistance of a plain (nonhealing) composite, revealing unique chemo-physical mechanisms that govern this behavior. Both fiber-debris accumulation in the molten poly(ethylene-co-methacrylic acid) (EMAA) healing agent, and waning interfacial chemical reactions between the EMAA and epoxy matrix, contribute. A Weibull distribution capturing this complex fracture recovery predicts an asymptotic healing limit above 40%, suggesting sustained repair is possible. Translating these newfound thermal remending results into real-world context, a modest quarterly self-healing schedule could maintain interlaminar fracture repair of FRP composites for over 125 y—well beyond the typical design life of many modern structures including aircraft and wind turbines. Thus, this latest self-healing paradigm effectively eliminates delamination as a failure mode.